Response of Turfgrass and Turfgrass Weeds to Herbicides - Joseph B. Unruh; Barry J. Brecke (EDIS)
Revised! ENH-100, a 10-page publication by J. B. Unruh and B. J. Brecke, provides tables to enhance understanding of turfgrass responses to herbicides. Includes tables showing tolerances of established turfgrasses to preemergence and postemergence herbicides; expected control of common weeds with preemergence and postemergence herbicides; common and scientific names of selected weeds, and common names of turf herbicides. Published by the UF Department of Environmental Horticulture, December 2006.